Crustal architecture and geodynamics of North Queensland, Australia: Insights from deep seismic reflection profiling - Korsch, R.; Huston, D.; Henderson, R.; Blewett, R.; Withnall, I.; Fergusson, C.; Collins, William; Saygin, E.; Kositcin, N.; Meixner, A.; Chopping, R.; Henson, P.; et al. (Elsevier BV, 2012)
A deep crustal seismic reflection and magnetotelluric survey, conducted in 2007, established the architecture and geodynamic framework of north Queensland, Australia. Results based on the interpretation of the deep seismic data include the discovery of a major, west-dipping, Paleoproterozoic (or older) crustal boundary, considered to be an ancient suture zone, separating relatively nonreflective, thick crust of the Mount Isa Province from thinner, two layered crust to the east. Farther to the east, a second major crustal boundary also dips west or southwest, offsetting the Moho and extending below it, and is interpreted as a fossil subduction zone. Across the region, the lower crust is mostly highly reflective and is subdivided into three mappable seismic provinces, but they have not been tracked to the surface. In the east, the Greenvale and Charters Towers Provinces, part of the Thomson Orogen, have been mapped on the surface as two discrete provinces, but the seismic interpretation raises the possibility that these two provinces are continuous in the subsurface, and also extend northwards to beneath the Hodgkinson Province, originally forming part of an extensive Neoproterozoic-Cambrian passive margin. Continuation of the Thomson Orogen at depth beneath the Hodgkinson and Broken River Provinces suggests that these provinces (which formed in an oceanic environment, possibly as an accretionary wedge at a convergent margin) have been thrust westwards onto the older continental passive margin. The Tasman Line, originally defined to represent the eastern limit of Precambrian rocks in Australia, has a complicated geometry in three dimensions, which is related to regional deformational events during the Paleozoic. Overall, the seismic data show evidence for a continental margin with a long history (Paleoproterozoic to early Mesozoic) but showing only limited outward growth by crustal accretion, because of a repeated history of overthrust shortening during repeated phases of orogenesis.